2002
DOI: 10.1103/physrevb.66.060508
|View full text |Cite
|
Sign up to set email alerts
|

Charge-density wave formation inSr14xCaxCu

Abstract: The electrodynamic response of the spin-ladder compound Sr14−xCaxCu24O41 (x = 0, 3, 9) has been studied from radiofrequencies up to the infrared. At temperatures below 250 K a pronounced absorption peak appears around 12 cm −1 in Sr14Cu24O41 for the radiation polarized along the chains/ladders (E c). In addition a strongly temperature dependent dielectric relaxation is observed in the kHz -MHz range. We explain this behavior by a charge density wave which develops in the ladders sub-system and produces a mode … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 31 publications
6
43
0
Order By: Relevance
“…In addition to the superconducting state, intensive studies have been devoted to the charge-density-wave (CDW) state, which is found in the parent system (x = 0) from optical measurements. 13,14,15 Further the global phase diagram for overall hole doping 16,17 shows that, with increasing the hole doping, the CDW state is suppressed and disappears at x ≃ 9, while the superconducting state emerges for x ≃ 11 and under pressure. From Raman scattering measurements, 18 it has been suggested that collective modes of the CDW state exist even in the highly doped superconducting material x = 12.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the superconducting state, intensive studies have been devoted to the charge-density-wave (CDW) state, which is found in the parent system (x = 0) from optical measurements. 13,14,15 Further the global phase diagram for overall hole doping 16,17 shows that, with increasing the hole doping, the CDW state is suppressed and disappears at x ≃ 9, while the superconducting state emerges for x ≃ 11 and under pressure. From Raman scattering measurements, 18 it has been suggested that collective modes of the CDW state exist even in the highly doped superconducting material x = 12.…”
Section: Introductionmentioning
confidence: 99%
“…In transitionmetal oxides, CO is a common phenomenon and an increasing number of dielectric measurements close to charge-ordering transitions are reported, specifically in lowdimensional systems having in mind the close analogy to the Peierls transition in metallic systems. Indeed, as mentioned above, a giant dielectric response has been detected in the insulating two-leg ladder Sr 14 Cu 24 O 41 [15,16] and in onedimensional (DI-DCNQ) 2 Ag [17]. Thus it seems promising to investigate also the insulating charge-ordered tetraselenide (NbSe 4 ) 3 I by broadband dielectric spectroscopy.…”
mentioning
confidence: 99%
“…It is possible that this mechanism is responsible for charge ordering in the telephone number compound observed in Ref. 7,6,9. As far as the CDW phases are concerned, the 2k F oscillations are always more relevant.…”
Section: Strong Coupling Phases and Order Parametersmentioning
confidence: 93%